2021
DOI: 10.1108/imds-12-2020-0756
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the differences across data quality classifications: a literature review and guidelines for future research

Abstract: PurposeNumerous data quality (DQ) definitions in the form of sets of DQ dimensions are found in the literature. The great differences across such DQ classifications (DQCs) imply a lack of clarity about what DQ is. For an improved foundation for future research, this paper aims to clarify the ways in which DQCs differ and provide guidelines for dealing with this variance.Design/methodology/approachA literature review identifies DQCs in conference and journal articles, which are analyzed to reveal the types of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 76 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…We search two leading databases, Web of Science and Scopus, which contain the majority of the academic literature in the field of business management (Haug, 2021; Núñez-Merino et al. , 2020).…”
Section: Methodsmentioning
confidence: 99%
“…We search two leading databases, Web of Science and Scopus, which contain the majority of the academic literature in the field of business management (Haug, 2021; Núñez-Merino et al. , 2020).…”
Section: Methodsmentioning
confidence: 99%
“…All the reviews were published between 1995 and 2023. Of the 20 excluded reviews, 5 (25%) were excluded because they were not specific to the health care ecosystem [ 18 , 44 - 47 ], 13 (65%) lacked relevant information related to our research objective [ 6 - 18 ], and 2 (10%) were published in a language other than English [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…One of the findings of the previously mentioned survey was that data users and producers are aware of the availability of qualified and community-approved data quality indicators to describe geodata quality. However, a recent review of scientific literature found 110 unique data quality classifications (Haug, 2021). Moreover, accepted and used quality indicators and classifications also vary within the ES discipline, for example, leading to a semantic gap between data producers and data users (Yang et al, 2013;Zhang et al, 2019) Moreover, we developed an interactive domain-specific tool (https:// geoku r-dmp.…”
Section: A Software Architecture To Implement a Generic Quality Registermentioning
confidence: 99%